Prevalence of serrated polyps: implications for significance as colorectal cancer precursors. (December 2013) - Tutticci, Nicholas J; Hewett, David G; Leggett, Barbara A
SUMMARY  Colorectal cancer remains a major cancer diagnosis, and a cause of mortality worldwide with screening and surveillance programs representing a significant healthcare commitment. The serrated pathway is responsible for 20–30% of colon cancers and evidence is accumulating for a major role in the relative failure of colonoscopy to provide high-level protection from cancer in the proximal colon. Although the significance of the serrated pathway and its precursor lesions are well established, the prevalence of the precursor lesions at colonoscopy is not. Multiple factors can impact attempts to accurately assess the prevalence of these lesions. This review discusses these factors and summarizes publications on sessile serrated adenoma and proximal serrated polyp prevalence.